2023
DOI: 10.7717/peerj.14872
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and musculoskeletal disorders—a cross-sectional study of teachers

Małgorzata Grabara

Abstract: Purpose Combined with insufficient physical activity (PA) prolonged and improperly performed sedentary work can lead to musculoskeletal disorders (MSDs). The aim of this study was (I) to evaluate the self-reported level of PA and the prevalence of MSDs in male and female teachers, and (II) to investigate the association between PA and MSDs in teachers in Polish primary and secondary schools. Methods The study included 254 teachers from primary and secondary schools from Upper Silesia, Poland, excluding physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…These studies have shown a clear significant association between physical activity habits and the prevalence of MSDs. Additionally, the lack of exercise has been found to increase the occurrence of these problems [ 20 , 21 ]. This could be attributed to the impact that physical activity has on the status of muscles, as it increases their mass and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown a clear significant association between physical activity habits and the prevalence of MSDs. Additionally, the lack of exercise has been found to increase the occurrence of these problems [ 20 , 21 ]. This could be attributed to the impact that physical activity has on the status of muscles, as it increases their mass and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have linked irregular exercise to low back pain (5,16,26). In fact, after performing a logistic regression, our study did not clearly demonstrate any association between irregular exercise to low back pain which correlates with the results of the study by Zamri and Yue (6,28).…”
Section: Discussionmentioning
confidence: 99%
“…The author also noticed that teachers with more musculoskeletal disorders-including back painwere less likely to participate in both vigorous and overall physical activity than those with fewer painful body parts. The lower back was also shown to be the most frequently affected area and to have the highest average pain intensity (16).…”
Section: Introductionmentioning
confidence: 97%
“…Physical activity levels were a pivotal component of our study, aligning with the guidelines established by the World Health Organization (WHO) for adults aged 18 to 65. Participants' physical activity was categorized into four distinct levels: low (such as walking which needs low effort), moderate (such as jogging which needs moderate effort (150 min/week)), high High intensity (such as running which needs high effort (75 min/week)) , or no physical activity( Sedentary) [15]. The study also investigated participants' habits during online education sessions, including whether they took regular breaks to stand, stretch, or walk ("yes" or "no") and their sitting posture "good" (neck and back straight while at work, using mobile phones and laptops) or "bad" during these sessions.…”
Section: Predictorsmentioning
confidence: 99%